Rasch Model Analysis to Develop Assessment Instruments for Student’s Science Process Skills on Chemical Bonding Material - Oktavianti, Femi; Aini, Faizah Qurrata (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The assessment of student’s science process skills (SPS) on chemical bonding material in schools does not yet meet the learning outcomes of the Merdeka curriculum, because the instruments used by teachers are more focused on knowledge aspects. The purpose of this research is to develop an assessment instrument for science process skills in the topic of chemical bonding. The type of this research is Research and Development (R&D) using the Rasch model modified by Liu. This research produced 18 questions tailored to the number of learning objectives in the chemical bonding material and the indicators of scientific process skills in the Merdeka curriculum, which consist of 1) observing, 2) questioning and predicting, 3) planning and conducting investigations. 4) processing, analyzing data and information, 5) evaluating and reflecting, and 6) communicating results. The logical validity test was conducted by 5 validators consisting of 3 chemistry lecturers from FMIPA UNP and 2 chemistry teachers from State Senior High School (SMAN) 1 Banuhampu. The raw validation data were analyzed using Minifaced software, which showed that the data were valid according to the model. The raw trial data on 60 students from SMAN 1 Banuhampu were analyzed using Ministep, showing that all questions met the criteria of being valid, reliable, and having good difficulty and discrimination indices according to Rasch. These results indicate that the developed instrument is effective in measuring students’ SPS on chemical bonding material and can be used to support learning based on a scientific approach.